Políticas e práticas curriculares em classes multisseriadas: realidade e desafios da alfabetização - Berger, Mara Gisele Medeiros Stefenon (2023)
This Master's thesis is linked to the research line Policies and Management of Basic and Higher Education of the Postgraduate Program, Professional Master's in Public Policies and Educational Management at the Federal University of Santa Maria (UFSM). It emphasizes problematizing the reality and challenges of multigrade classes in the post-pandemic period, with the aim of analyzing the impacts arising from the situation on the literacy process from the perspective of current curricular policies. To this end, the general objective is to understand how literacy curricular policies and practices are developed in multigrade classes. Likewise, the specific objectives are the following: analyze literacy curriculum policies; problematize the curricular organization of literacy in multigrade classes and highlight literacy practices designed to teach children. The methodology used was Case Study research, plus bibliographical research and documentary analysis, based on the survey of theoretical references already analyzed and published through written and electronic media, such as books, scientific articles and legislation relevant to the research topic. To search for information, semi-structured interviews were carried out with professionals who carry out educational activities in this context and analysis of official documents with curricular guidelines. The interviews were carried out with teachers from the education network who teach in multigrade classes. With this, it is understood that literacy curricular policies and practices become even more complex in multigrade classes, since several grades/years are involved in a single class in the classroom, at the same time and curricular space under the responsibility from a single teacher. It is evident that planning and the issue of time were well emphasized by the educators, as well as the impact of the pandemic on children's literacy, making progress in reading and writing difficult. In view of this, a technical product was created in the format of a Facebook page, with weekly posts and tips for lesson planning and studies on the topic to assist educators, parents and school management in curriculum development.